Identifying metabolite ions of peptide drugs in the presence of an in vivo matrix background. (March 2012) - Cuyckens, Filip; Dillen, Lieve; Cools, Willy; Bockx, Marc; Vereyken, Liesbeth; de Vries, Ronald; Mortishire-Smith, Russell J
Background: Peptides represent a growing class of potential drugs. Information on metabolic clearance can be valuable for peptide drug development but different challenges are encountered with the identification of peptide metabolites in comparison to the process used for small-molecule therapeutics.Results: Enfuvirtide was selected as a test compound and dosed intravenously at 2 mg/kg to rats. Plasma samples were collected and analyzed on two different quadrupole-TOF instruments in positive and negative ion modes. Different post-acquisition processing tools were evaluated to identify the metabolites of a peptide drug in the presence of an in vivo matrix. Charge state filtering and ion mobility extraction were applied to reduce the matrix background and combined with more comprehensive software tools generally used for large molecule analyses as well as tools designed for small-molecule metabolite identification work.Conclusion: Both ion mobility spectrometry and charge state filtration proved to be successful in extracting peptide ions and significantly reducing background signals. Both small- and large-molecule software tools contain specific capabilities that could be usefully combined in a single package for peptide metabolite identification.